The spreading of X inactivation into autosomal material of an x;autosome translocation: evidence for a difference between autosomal and X-chromosomal DNA. - White, W M (1998)
X inactivation involves initiation, propagation, and maintenance of genetic inactivation. Studies of replication timing in X;autosome translocations have suggested that X inactivation may spread into adjacent autosomal DNA. To examine the inactivation of autosomal material at the molecular level, we assessed the transcriptional activity of X-linked and autosomal loci spanning an inactive translocation in a phenotypically normal female with a karyotype of 46,X,der(X)t(X;4)(q22;q24). Since 4q duplications usually manifest dysmorphic features and severe growth and mental retardation, the normal phenotype of this individual suggested the spreading of X inactivation throughout the autosomal material. Consistent with this model, reverse transcription-PCR analysis of 20 transcribed sequences spanning 4q24-qter revealed that three known genes and 11 expressed sequence tags (ESTs) were not expressed in a somatic-cell hybrid that carries the translocation chromosome. However, three ESTs and three known genes were expressed from the t(X;4) chromosome and thus "escaped" X inactivation. This direct assay of expression demonstrated that the spreading of inactivation from the adjoining X chromosome was incomplete and noncontiguous. These findings are broadly consistent with the existence of genes known to escape inactivation on normal inactive X chromosomes. However, the fact that a high proportion (30%) of tested autosomal genes escaped inactivation may indicate that autosomal material lacks X chromosome-specific features that are associated with the spreading and/or maintenance of inactivation.